2020
DOI: 10.3390/microorganisms8091397
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Assignment of the Fungicolous Hypoxylon invadens (Ascomycota, Xylariales) and Investigation of its Secondary Metabolites

Abstract: The ascomycete Hypoxylon invadens was described in 2014 as a fungicolous species growing on a member of its own genus, H.fragiforme, which is considered a rare lifestyle in the Hypoxylaceae. This renders H.invadens an interesting target in our efforts to find new bioactive secondary metabolites from members of the Xylariales. So far, only volatile organic compounds have been reported from H.invadens, but no investigation of non-volatile compounds had been conducted. Furthermore, a phylogenetic assignment follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The Daldinia sequences are monophyletic. This cladogram supports a study by Becker et al (2020), who reported that Xylariaceae is separated into numerous main clades of Hypoxylon and Daldinia taxa, forming another distinct clade accommodated in the Hypoxylaceae. Daldinia and Hypoxylon are included in a distinct family of filamentous Ascomycota, Xylariales, containing taxa of Daldinia and Hypoxylon as a sizable monophyletic group (Hsieh et al 2005;Becker et al 2020).…”
Section: Molecular Phylogeny and Ic50 Values Of Selected Endophytic F...supporting
confidence: 91%
“…The Daldinia sequences are monophyletic. This cladogram supports a study by Becker et al (2020), who reported that Xylariaceae is separated into numerous main clades of Hypoxylon and Daldinia taxa, forming another distinct clade accommodated in the Hypoxylaceae. Daldinia and Hypoxylon are included in a distinct family of filamentous Ascomycota, Xylariales, containing taxa of Daldinia and Hypoxylon as a sizable monophyletic group (Hsieh et al 2005;Becker et al 2020).…”
Section: Molecular Phylogeny and Ic50 Values Of Selected Endophytic F...supporting
confidence: 91%
“…The combined rooted phylogenetic tree showed a clade consisting of the core members of the Hypoxylaceae, such as Hypoxylon, Daldinia, Pyrenopolyporus, Hypomontagnella, Jackrogersella, Rostrohypoxylon, Thamnomyces and Ruwenzoria with medium BS and high PP support (1/90), which was placed in a sister position to a clade consisting of members of Parahypoxylon gen. nov., and Durotheca (Hypoxylaceae) at the base of the tree with strong support (1/100). The genus Hypoxylon could be confirmed as paraphyletic, as has been described already by Wendt et al (2018), Lambert et al (2019), andBecker et al (2020). The sequences assigned to Parahypoxylon ruwenzoriense formed a highly supported (1/100) cluster with the sequences derived from Parahypoxylon papillatum.…”
Section: Phylogenetic Analysessupporting
confidence: 72%
“…The fungicolous H. invadens , which was only described in 2014, exhibits a unique lifestyle by growing on a member of its own genus, H. fragiforme [ 102 ]. So far, only volatile organic compounds have been described from H. invadens [ 103 ], but a recent investigation into its secondary metabolites revealed the known naphthoquinones flaviolin ( 73 ) and 3,3′-biflaviolin ( 74 ) to be produced in submerged cultures [ 104 ]. Only known as products of the melanin biosynthesis when the underlying pathway was actively influenced (e.g.…”
Section: Novel Secondary Metabolites From Species Of the Hypoxylaceaementioning
confidence: 99%